2007
DOI: 10.1038/sj.onc.1210943
|View full text |Cite
|
Sign up to set email alerts
|

Enforced epithelial expression of IGF-1 causes hyperplastic prostate growth while negative selection is requisite for spontaneous metastogenesis

Abstract: The insulin-like growth factor-1 (IGF-1) signaling axis is important for cell growth, differentiation and survival and increased serum IGF is a risk factor for prostate and other cancers. To study IGF-1 action on the prostate, we created transgenic (PB-Des) mice that specifically express human IGF-1 des in prostate epithelial cells. This encodes a mature isoform of IGF-1 with decreased affinity for IGF binding proteins (IGFBP) due to a 3-amino acid deletion in the N terminus. Expression of IGF-1 des was suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…Recently, we reported that enforced expression of IGF-I in prostate epithelium could promote preneoplastic growth but was insufficient to cause carcinoma (18). As well, crossing the lit mice with TRAMP (28) showed that although chronically reduced systemic IGF-I and GH expression could significantly delay tumor-related death, the direct role of IGF-I signaling at the level of the prostate epithelium was not specifically addressed nor was the relative contribution of reduced GH levels to prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that enforced expression of IGF-I in prostate epithelium could promote preneoplastic growth but was insufficient to cause carcinoma (18). As well, crossing the lit mice with TRAMP (28) showed that although chronically reduced systemic IGF-I and GH expression could significantly delay tumor-related death, the direct role of IGF-I signaling at the level of the prostate epithelium was not specifically addressed nor was the relative contribution of reduced GH levels to prolonged survival.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our data indicate that any decrease in circulating IGF-I in combination with changes to p53 that would physiologically accompany normal aging would provide selective advantage to transformed epithelial cells that could overcome the IGF-IR-mediated differentiation block and progress toward more invasive and disseminated forms of carcinoma. We have previously proposed the hurdle hypothesis to explain how factors that contribute to the height of the differentiation ''hurdle'' in essence will determine how aggressive a cancer must become to overcome the differentiation barrier/blockade to achieve malignant transformation (18). Because abrogation of functional IGF-IR expression actually promoted earlier emergence of more aggressive, less-differentiated carcinomas in a p53-compromised model of prostate cancer, the current data support the hypothesis that titration of IGF-IR signaling reduces the prodifferentiation block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF promotes epithelial growth in tissue culture studies and in vivo (Cohen et al, 1991;Plymate et al, 1996). IGF overexpression exhibits a potent growth-promoting effect for IGF in the prostate and results in hyperplasia (DiGiovanni et al, 2000;Kaplan-Lefko et al, 2008). Further, Ruan and Kleinberg demonstrated that IGF-I is required for prostate development (Ruan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Augmented steroidal signaling and mesenchymal-epithelial interactions are required for the normal as well as pathological growth of the prostate gland (Marker et al, 2003). However, current literature indicates that apart from steroids, peptides and lipids are also playing a crucial role in the pathogenesis of BPH (Cai et al, 2001;Culig et al, 1996;Escobar et al, 2009;Kaplan-Lefko et al, 2008;Rahman et al, 2007;Rick et al, 2011;Story, 1995;Vikram et al, 2010c). Even if the effects of peptides and lipids on the growth of the gland is milder as compared to that of steroids, chronic change in their levels either due to dietary habit or genetic predispositions can significantly contribute to the initiation and/or progression of the disease over a period of time.…”
Section: Introductionmentioning
confidence: 99%